Analisis Faktor- Faktor Yang Memengaruhi Alih Fungsi Lahan Sawah Ke Non Sawah Di Kabupaten Klaten - Nurrahma, Alifia Fauziyah; Darsono, Darsono; Barokah, Umi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
The area of rice fields in Klaten Regency has decreased every year, this is in line with the increase in population and the non-agricultural sector that requires land so that the function of rice fields to non-rice fields is converted to meet the demand for this land. This research aims was to examine the rate of conversion of rice fields in Klaten Regency, the development of rice fields in Klaten Regency and to find out the factors that influence the conversion of rice fields in Klaten Regency. The basic method of this research is descriptive and quantitative analysis methods. The type of data used is secondary data in the form of time series data for 1990-2019. The quantitative analysis method used is the calculation of the partial rate of land conversion, analysis of the influencing factors using multiple linear regression analysis based on OLS (Ordinary Least Square). The results showed that the rate of conversion of rice fields in Klaten Regency during 1990-2019 experienced a fluctuating conversion of rice fields, the area of decreasing rice fields was 5.5% or 2,155 ha and the average conversion rate was 0.18% with over the function of rice fields 71.3 Ha per year. Based on multiple linear regression analysis (Ordinary Least Square) with a confidence level of 95%, it is known that the factors that influence the conversion of rice fields to non- rice fields in Klaten Regency are residential, current price PDRB, and population.